Juridical Review of Legal Vacuum in the Regulation of Interfaith Marriage in Indonesia - Raja Zulkifli; Doni Gusmardi; Fadlan Fadlan (International Journal of Law and Society, 2025)
Interfaith marriage in Indonesia represents a complex legal challenge characterized by significant regulatory ambiguity and constitutional tensions. This juridical research investigates the existing legal vacuum surrounding interfaith marriage, examining the critical gaps in current legislation that impede comprehensive legal protection for interfaith couples. Utilizing a normative juridical approach with legislative and conceptual analysis, the study explores the intricate intersections between religious diversity, individual rights, and legal frameworks.The research reveals substantial deficiencies in the current legal system, highlighting the absence of specific regulations governing interfaith marriage. Key findings demonstrate the urgent need for a comprehensive legislative framework that balances religious pluralism, constitutional principles, and individual human rights. The study identifies critical challenges, including conflicts between existing legal provisions, social perceptions, and constitutional guarantees of religious freedom.Methodologically grounded in progressive legal theory and human rights principles, the research provides a critical analysis of the existing legal landscape. Comparative insights from international jurisdictions underscore the necessity of legal reform. The findings recommend the development of nuanced legislation that respects individual choice while maintaining social harmony.The study concludes that Indonesia requires a transformative approach to interfaith marriage regulation, emphasizing legislative reforms, public education, and the establishment of robust legal mechanisms that protect individual rights within the context of religious and cultural diversity.